Pérez de la Fuente, Oscar; Falcão, Monique y Oliva Martínez, J. Daniel (eds.) Struggles for Recognition. Cultural Pluralism and Rights of Minorities, Madrid: Dykinson, 2020, 286 pp. - Jesús Mora (Cuadernos Electrónicos de Filosofía del Derecho)
Recensión de la obra: Pérez de la Fuente, Oscar; Falcão, Monique y Oliva Martínez, J. Daniel (eds.) Struggles for Recognition. Cultural Pluralism and Rights of Minorities, Madrid: Dykinson, 2020, 286 pp.